2012
DOI: 10.1111/j.1439-0426.2012.01969.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of starvation and re-feeding on growth performance and content of plasma lipids, glucose and insulin in cultured juvenile Persian sturgeon (Acipenser persicusBorodin, 1897)

Abstract: Summary The effect of starvation and subsequent re‐feeding to satiation on compensatory growth performance, insulin and blood serum values were investigated in juvenile Persian sturgeon (Acipencer persicus) with an average weight 108.04 ± 0.28 g (mean ± SEM) and in the same rearing condition over an 8‐week period. Sturgeons were allocated to one of five feeding treatments: controls (C, continuous feeding), W1 (1 week starvation), W2 (2 weeks starvation), W3 (3 weeks starvation) and W4 (4 weeks starvation), fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
34
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 39 publications
9
34
1
1
Order By: Relevance
“…Body weight decreased systematically over the 4-wk period, with the 100% OFR group exhibiting an approximate 64% increase in body weight, while the 12.5% OFR group lost 11% in accordance with previous studies in feed-deprived, larger (mean 5 SE, 377516 g) white sturgeon and smaller (mean 5 SE, 108 5 0.3 g) Persian sturgeon (Acipenser persicus) juveniles Yarmohammadi et al 2012). Following the 4-wk feed restriction trial, the 100% OFR group exhibited whole-body lipid values similar to those of juvenile green sturgeon (mean 5 SE, 30 5 2 g; Lee et al 2011) fed using the same optimum feeding rate model (Cui and Hung 1995).…”
Section: Effect Of Feed Restriction On Nutritional Statussupporting
confidence: 87%
“…Body weight decreased systematically over the 4-wk period, with the 100% OFR group exhibiting an approximate 64% increase in body weight, while the 12.5% OFR group lost 11% in accordance with previous studies in feed-deprived, larger (mean 5 SE, 377516 g) white sturgeon and smaller (mean 5 SE, 108 5 0.3 g) Persian sturgeon (Acipenser persicus) juveniles Yarmohammadi et al 2012). Following the 4-wk feed restriction trial, the 100% OFR group exhibited whole-body lipid values similar to those of juvenile green sturgeon (mean 5 SE, 30 5 2 g; Lee et al 2011) fed using the same optimum feeding rate model (Cui and Hung 1995).…”
Section: Effect Of Feed Restriction On Nutritional Statussupporting
confidence: 87%
“…The results are in accordance with Yarmohammadi et al, (2015). However, Cho (2009) andCho et al, (2006), Cho & Cho (2009) reported no significant differences in ALT and AST levels of olive flounder subjected to 8 weeks fasting between fed and starved groups; but, was increasingly significant in olive flounder after 4 weeks starvation.…”
Section: Resultssupporting
confidence: 76%
“…Additionally, full compensation (Kim and Lovell, 1995;Gaylord and Gatlin, 2001;Zhu et al, 2001Zhu et al, , 2005Qin, 2003, 2004;Nikki et al, 2004;Oh et al, 2007) and over compensation levels have also been obtained (Hayward et al, 1997;Turano et al, 2007). Yarmohammadi et al, (2015) Findings showed that the juvenile Persian sturgeon starved for 1,2, and 4 weeks showed complete compensatory growth while fish starved for 3 weeks showed partial compensatory growth. This means that the compensatory response depends on the length of feed deprivation.…”
Section: Resultsmentioning
confidence: 73%
“…Only short-term (4e5 weeks) effects of starvation on white epaxial muscle have been studied in white sturgeon Acipenser transmontanus (Kiessling et al, 1993). In addition, some other studies on lake sturgeon A. fulvescens (Gillis and Ballantyne, 1996), white sturgeon (Hung et al, 1997), Chinese sturgeon Acipenser sinensis (Liu et al, 2011), beluga Huso huso (Falahatkar et al, in press), Adriatic sturgeon Acipenser naccarii (Furné et al, 2012) and Persian sturgeon Acipenser persicus (Yarmohammadi et al, 2012) showed the effect of starvation on some morphoephysiological parameters.…”
Section: Introductionmentioning
confidence: 98%